ANALYSIS USABILITY OF USER EXPERIENCE OF THE SRAWUNG WITH THE USER EXPERIENCE QUESTIONNARE (UEQ) METHOD - Achmad Azhar Rifan Nugroho; Erwin Apriliyanto (Julia: Jurnal Ilmu Komputer An Nuur, 2023)
An important aspect when evaluating the quality of an application is usability. The quality level of usability of the application is determined by how easy the user of the application uses it. Applications and products with good usability usually have many loyal users. Conversely, if an app has a low level of usability, users will inevitably give up and switch to another app that has similar functionality. The application analyzed in this study is an android application called Srawung with video conferencing features. In this study, to assess the quality of usability used the User Experience Questionnaire (UEQ) method. The user experience questionnaire (UEQ) uses a six-dimensional scale such as attractiveness, acuity, efficiency, dependability, stimulation, and novelty. Data collection is done by distributing forms to Srawung application users who are also respondents. The questionnaire consists of several questions as indicators of research variables from six dimensions. The result of user satisfaction analysis is that application users can use the Srawung application better and which indicators are good and which are not.